Research and development of medical/nursing care support system using Radar sensing technology and Hybrid WSN - Tsuge, Akira; Nuno, Fusao; Yamaguchi, Kazuhiro; Furuya, Yasuaki; Iguchi, Atsushi; Matsue, Hideaki (2020 23rd International Symposium on Wireless Personal Multimedia Communications (WPMC), 2020)
Not only in developed countries, but as the population ages globally, staff resources are becoming increasingly scarce at medical and nursing care sites. Under such circumstances, COVID-19, which occurred in 2020, faced the crisis of collapsing medical practice on a global scale. What has made the world feel through the threat of the COVID-19 pandemic is the importance about the prevention of infection for medical and care staff. From this view point, it is considered to be extremely effective to recognize the condition of patients and care recipients without contact as much as possible. In this research, we will collect living behavior and vital data such as respiration and heartbeat in a facility without contact by combining sensing technology using 24GHz radar and multiple Wireless Sensor Network systems. We propose a hybrid wireless sensor network platform for medical and nursing care sites that can grasp the conditions related to patients and care recipients in each zone from the inside of the facility to the surrounding area and the suburbs. In the facility, a high-speed Wi-Fi mesh network will be used to build a network that can share the 24GHz radar signal data of each room in real time. One of our challenge is the detection of the behavior, respiration and heartbeat of the occupants by analyzing these radar signals without using a camera which is difficult to install in the field due to privacy protection issues, and without the subject wearing a wearable sensor directly. If it is detected that the patient or resident has gone out, the situation of the resident's walking area around the facility can be detected by using the Wi-SUN FAN mesh network in the area around the facility with a radius of about 500 m. In addition, in the suburbs area, GPS information using a LoRaWAN small terminal will enable centralized management of location information of residents without smartphones. As described above, in this study, we propose the Hybrid Wireless Sensor Network platform for medical and nursing care sites by utilizing 24 GHz radar sensing technology and hybrid wireless sensor network technology. We will report the results of a demonstration experiment of this system in an actual nursing facility.